2020
DOI: 10.5897/ijeaps2019.0643
|View full text |Cite
|
Sign up to set email alerts
|

Balancing work, family and personal life: Perspectives of female staff at the College of Distance Education, University of Cape Coast, Ghana

Abstract: The study examined how female staff of the College of Distance Education (CoDE), University of Cape Coast (UCC) balance work, family and personal life roles, amidst their busy work schedules. A 21-item well-structured questionnaire was developed to collect primary data. Using the convenient sampling technique, 32 female staff was selected for the sample. Statistical tools such as percentages, mean, standard deviation as well as regression analysis were used to examine the relationship between organizational, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The study of Gragnano et al (2020) also confirmed that workers considered health as important as a family in the WLB. Some Recent studies also affirmed this finding (Clara, 2020;Denson et al, 2018;Jackson & Bridgstock, 2019;Rusman et al, 2020;Szelényi & Denson, 2019).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The study of Gragnano et al (2020) also confirmed that workers considered health as important as a family in the WLB. Some Recent studies also affirmed this finding (Clara, 2020;Denson et al, 2018;Jackson & Bridgstock, 2019;Rusman et al, 2020;Szelényi & Denson, 2019).…”
Section: Discussionmentioning
confidence: 67%
“…Brue (2019) reported that WFB has an influence on the job performance and satisfaction of the employee. Similarly, Clara (2020) reported that WFB promotes the job commitment of workers, reduces the rate of absenteeism and enhances the satisfaction of the employee. Felicity et al (2013) conclude that WFB is a strong determinant of employee commitments and satisfaction in an organization.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, personal endeavors to balance time are: (a) establishing priorities among tasks and roles; (b) planning and scheduling work, personal, social, and familial activities; (c) building boundaries between work and social activities; and (d) organizing vacations; among others [59][60][61][62][63].…”
Section: Rule 8: Balance Time To Perform Roles In Society and Familymentioning
confidence: 99%